Pengaruh Green Productivity Sebagai Mediasi Pada Lingkungan Kerja, Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Karyawan Bagian Produksi PT Indofood CBP Sukses Makmur TBK Cabang Palembang - Yun Suprani; Muhammad Said; Yusro Hakimah; Mia Anggraini (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
This study aims to determine the effect of Green Productivity as a mediation on the work environment andwork safety on the performance of employees of the Production Department of PT Indofood CBP Sukses MakmurTBK Palembang Branch. The population in this study were employees of the production section of PT Indofood CBPSukses Makmur TBK Palembang Branch. The population is 73 people. The data analysis used is the StructuralEquation Model (SEM) analysis method which is operated through the Partial Least Square (PLS) program. Theresults of this study indicate that there is an effect of Green Productivity on. Work Environment and Employee Safety.The R2 value for the Green Productivity latent variable as a mediating variable is 0.930, which means that thisvalue identifies that variations in Employee Green Productivity can be explained by exogenous latent variables(Work Environment and Work Safety) of 93% while the remaining 7% is explained by other variables and the valueof R2 for the performance latent variable of 0.965, which means that this value identifies that variations in performancecan be explained by exogenous variables of 96.5% while the remaining 3.5% is explained by variables notpresent in the study.